Answer:
B
Step-by-step explanation:
Answer:
(1/4)*(e⁶ - 7)
Step-by-step explanation:
a) Given
x − y = 0 if x = 0 ⇒ y = 0
x − y = 2 if x = 0 ⇒ y = -2; if y = 0 ⇒ x = 2
x + y = 0 if x = 0 ⇒ y = 0
x + y = 3 if x = 0 ⇒ y = 3; if y = 0 ⇒ x = 3
then we show the region R in the pics 1 and 2.
b) We make the change of variables as follows
u = x + y
v= x - y
If
x - y = 0 ⇒ v = 0
x − y = 2 ⇒ v = 2
x + y = 0 ⇒ u = 0
x + y = 3 ⇒ u = 3
Where u is the horizontal axis and v is the vertical axis, the new region S is shown in the pic 3.
c) We evaluate ∫∫R (x + y)*e∧(x² - y²)dA
The procedure is shown in the pic 4, where we have to calculate the Jacobian in order to use it to get the answer.
Step-by-step explanation:
452
Answer: -6
Step-by-step explanation:
Answer:
my best guess even though no answers i would say bout 12
Step-by-step explanation: